2011
DOI: 10.1080/11263504.2010.539851
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of salt-induced ionic, osmotic and oxidative stresses inCajanus cajannodules by AM inoculation

Abstract: Legume-Rhizobium symbiotic nitrogen (N 2 ) fixation plays a critical role in sustainable nitrogen management in agriculture. The nitrogen fixed by the root nodules not only affects the nitrogen cycle of nature, but is also of great economic importance. A number of physiological and biochemical processes in the nodules are affected by salt stress. The objective of this study was to evaluate the role of arbuscular mycorrhiza (AM) in moderating toxic effects of salt stress on nodular metabolism in Cajanus cajan (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 64 publications
0
24
0
Order By: Relevance
“…These are not merely non-toxic cellular osmolytes but they can also stabilize the structures and activities of protein complexes and maintain the integrity of membrane against the damaging effects of excessive salt (Gorham ,1995). It was found that at higher salinity levels the glycine betaine content of AM treated pigeon-pea plants was about 2-fold greater than that of non-AM plants ( Manchanda and Garg, 2011). Enzymes activity: There is accumulating evidence that production of reactive oxygen species (ROS) is a major damaging fac-tor in plants exposed to different environmental stresses, including salinit.…”
Section: Biochemical Changesmentioning
confidence: 86%
See 1 more Smart Citation
“…These are not merely non-toxic cellular osmolytes but they can also stabilize the structures and activities of protein complexes and maintain the integrity of membrane against the damaging effects of excessive salt (Gorham ,1995). It was found that at higher salinity levels the glycine betaine content of AM treated pigeon-pea plants was about 2-fold greater than that of non-AM plants ( Manchanda and Garg, 2011). Enzymes activity: There is accumulating evidence that production of reactive oxygen species (ROS) is a major damaging fac-tor in plants exposed to different environmental stresses, including salinit.…”
Section: Biochemical Changesmentioning
confidence: 86%
“…Peroxidase (POX) and catalase (CAT) are involved in the defense mechanisms of plants in response to pathogens either by their participa-tion in cell wall reinforcement, or by their antioxidant role in the oxidative stress generated during plant pathogen interaction (Mehdy, 1994). Manchanda and Garg (2011) reported that low and moderate salinity further increased the antioxidant enzymes activity in the nodules of mycorrhizal-stressed Cajanus cajan plants. Soybean plants inoculated with salt pretreated mycorrhizal fungi showed salt adaptation through increased SOD and POX activity in shoots, to those inoculated with the nonpretreated fungi (Ghorbanali et al, 2004).…”
Section: Biochemical Changesmentioning
confidence: 99%
“…Osmoregulation can be also achieved with betaines and with sugars. Both are increased in mycorrhizal plants and were suggested as being involved in salt tolerance (Porcel and Ruiz-Lozano 2004;Manchanda and Garg 2011).…”
Section: Other Mechanismsmentioning
confidence: 99%
“…Mycorrhiza is a symbiotic association between plant roots and fungi. Arbuscular mycorrhizal fungi promote salinity tolerance by utilizing various mechanisms such as accumulation of compatible solutes and production of higher antioxidant enzymes (Manchanda and Garg, 2011). Mycorrhizal fungi increase the sugar content of the host plant by hydrolysis of starch to sugars and preventing structural changes in soluble protein .…”
Section: Introductionmentioning
confidence: 99%